Dyadic Relational Quality and Communication Satisfaction among Universiti Utara Malaysia (UUM) Employees - Aida Suhana, Abdul Hamid (2010)
This study attempts to investigate the dyadic relations quality and communication satisfaction among employees of Universiti Utara Malaysia (UUM). Specifically, these studies examine the relationship between Leader-member-exchange (LMX) quality and subordinates communication satisfaction. Multiple regression analysis used to examine the relationship among 130 employees in UUM. Findings indicate that affect, loyalty, perceived contribution and respect are strongly related to subordinate’s communications satisfaction. The implications of this study discussed further are elaborated.